Electrochemical power sources : fundamentals, systems, and applications : hydrogen production by water electrolysis - Smolinka, Tom; Garche, Jurgen (Elsevier, 2022)
Electrochemical Power Sources: Fundamentals, Systems, and Applications: Hydrogen Production by Water Electrolysis offers a comprehensive overview about different hydrogen production technologies, including their technical features, development stage, recent advances, and technical and economic issues of system integration. Allied processes such as regenerative fuel cells and sea water electrolysis are also covered. For many years hydrogen production by water electrolysis was of minor importance, but research and development in the field has increased significantly in recent years, and a comprehensive overview is missing. This book bridges this gap and provides a general reference to the topic. Hydrogen production by water electrolysis is the main technology to integrate high shares of electricity from renewable energy sources and balance out the supply and demand match in the energy system. Different electrochemical approaches exist to produce hydrogen from RES (Renewable Energy Sources).